Caries Prevalence and Eating Habits in Infants in Southeastern Brazil - Oliveira, Josy dos Santos de; Gasque, Kellen Cristina da Silva; Nogueira, Denismar Alves; Costa, Lucas Bruzadelli Paulino da; Lima, Daniela Coelho de; Dias Caldeira, François Isnaldo; Oliveira, Daniela Silva Barroso de (ARCHIVES OF HEALTH INVESTIGATION, 2021)
Introduction: In the last decades, great emphasis has been given to early dental care. Dentistry for Babies has been gaining more and more space within current dentistry, to promote reduction of caries incidence and improvement of collective consciousness, especially of parents or guardians, regarding to oral care, hygiene habits and diet. Objective: To evaluate the prevalence of caries in infants aged 13 to 36 months attending a university pediatric dental clinic in Southeastern Brazil and correlate these data with their eating habits. Methods: Parents or guardians responded to a semi-structured questionnaire approaching eating habits of these infants and their exposure to foods with cariogenic potential. In addition, the dmf-t index and the risk of caries were evaluated considering alpha of 0.05. Results: Mean dmf-t index was 1.25. Most babies presented a high 50% risk for the development of caries disease. The intake of foods with protective potential for dental caries was present in the diet of 93.3% of infants. Despite of that, 73.3% of the infants ate foods with hidden sugar and 53.3% took syrup or suspension medications.Results were statistically different (p = 0.017) between infants who received breastfeeding and their dmf-t indexes. Conclusion: Majority of infants had inadequate dietary patterns, exaggerated exposure to liquids or foods with cariogenic potential, evidenced by the elevated dmf-t index. Also, breastfeeding was correlated to higher risks to develop dental caries.